ANALYSIS OF THE IMPLEMENTATION OF THE PANCASILA DIMENSIONAL STUDENT PROFILE (FAITH, DELIBERATION TO THE ALMIGHTY GOD AND NOBLE IMAGES) AT MTSN 1 KERINCI - Qutrul Nada, Fitria; Pandapotan Simaremare, Tohap; Utami, Sundari (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
The background to this research reveals the problems that occur at MTsN 1 Kerinci, where the Pancasila Student Profile program has not been fully implemented and is still less visible in practice. Most teachers experience difficulties in organizing appropriate activities, especially in aligning the implementation of the Pancasila Student Profile with effective and relevant projects or activities to support these values.This research aims to analyze the implementation and inhibiting factors in implementing the dimensions of Faith, Fear of God Almighty, and Noble Character in the Pancasila Student Profile. This research was conducted at MTsN 1 Kerinci, Air Hangat Timur District, Kerinci Regency. Data collection techniques used include observation, interviews and documentation. The implementation of the values ​​of being devoted to God Almighty and having noble morals has been effective. In the P5 Program, teachers act as planners, facilitators, companions, supervisors and moderators. As part of the implementation of the P5 Teaching Module with the theme